Peran Job Stress dan Job Satisfaction Terhadap Turnover Intention Pada Karyawan Restoran - Wiastuti, Rachel Dyah; Stevani, Intan; Moerti, Indrawati (Politeknik Pariwisata NHI Bandung, 2023)
Purpose of the study: The objective of this study is to analyze the role of job satisfaction on the as the mediating role between job stress and turnover intention of restaurant employee. Design: The research adopt quantitative method with survey. Questionnaire was distributed face to face to all 16 employees of John & James Resto located in Green Lake City Jakarta and Bumi Serpong Damai Tangerang. Likert scale was employed to 30 measurement items in order to test three research hypotheses that later analyze using path analysis. Findings: Employee job stress negatively influence job satisfaction, while job satisfaction on the other hand, also negatively influence turnover intention. However, the mediating role of job satisfaction has no positive effect on job stress and employee turnover intention. Job satisfaction acts as a perfect mediation based on direct effects and indirect effects. This means that after being mediated by job satisfaction, when job stress increases, turnover intention does not immediately increase because there are job satisfaction factors that make the desire to leave work decrease. Research Limitations/ Implications: This research was limited to only one particular restaurant brand. Thus, it can be implied to similar business model which are small to medium size capacity, self- managed, dan local market based, that in turn in light the way to reduce employee turnover could be managed through employee job stress and employee job satisfaction. Novelty/ Originality of the study: This research contribute to the literature of human resources by using different measurement scale combining from several references to measure job satisfaction and turnover intention that specified for hospitality context.